TRANSFORMASI PLASMID REKOMBINAN pRI_101-AN MEMBAWA SISIPAN GEN cryIII MELALUI Agrobacterium tumefaciens - Febriana Dwi Wahyuni; Muhamad Amza Sidiq; Seprianto Seprianto; Henny Saraswati (BERITA BIOLOGI, 2022)
Sweet potato is a plant that give many benefits because of its high carbohydrate content and is an alternative food source. Behind the benefits of sweet potatoes, there is a threat of pest attack that can cause a decrease in production of up to 19.91%. Sweet potato weevil attack on the leaves, stalks, stems, and tubers. The solution to against this pest attack is by engineering using the cry III gene mediated by A. tumefaciens. The aim of this study was to transform a recombinant plasmid carrying the insertion of the cry III gene into A. tumefaciens cells. The results showed that the recombinant plasmid pRI_101-AN carrying the insertion of the cry III gene was successfully transformed into A. tumefaciens cells by electroporation method by producing 36 recombinant clones on LB media with neomycin and kanamycin antibiotics. Results of colony PCR, DNA bands measuring 1900 bp were successfully amplified using gene-specific primers. Results of the isolation of plasmid DNA bands measuring 12000 bp were obtained from the results of electrophoresis. This size corresponds to the recombinant plasmid pRI_101-AN-cry III.